Meet Dave - Berg, Jon; Friendly, David T.; Komarnicki, Todd; Greenberg, Robbie; Corbett, Bill, 1960-; Robbins, Brian, 1963-; Murphy, Eddie, 1961-; Banks, Elizabeth, 1974-; Union, Gabrielle; Caan, Scott, 1976-; Helms, Ed; Myers, Austin Lynd (20th Century Fox Home Entertainment, 2008)
Josh lives in New York City. Through his telescope, he watches a baseball-sized metal ball approaching Earth from the sky. It lands in his room. Months later, a massive fireball crash lands in Liberty City. The human looking craft is controlled by 100 one-inch tall aliens. Officer Dooley is a superstitious cop searching for the space ship. The aliens are seeking a way to save their planet and to do that they need salt. Now they need to recover the metal ball in order to produce the salt using the oceans of the Earth. The Captain spends time with Josh and Gina, and realizes that humans are more advanced than they thought.